Factors Affecting Compliance With Paying Personal Income Tax In Muara Bangkahulu District - Klara Mega Utari Panjaitan; Karona Cahya Susena; Kamelia Astuty (Penerbit Jurnal Indonesia, 2024)
This research aims to determine the factors that influence compliance with paying personal income tax in Muara Bangkahulu District. This research is a quantitative descriptive study using primary data collected through distributing questionnaires to 10,943 taxpayers registered at the Pratama Bengkulu Satu Tax Service Office (KPP) in Muara Bangkahulu District. The sampling technique used was convenience sampling. The data used is primary data in the form of respondents' answers and processed using SPSS 25.The results of this research show that knowledge about taxes, service quality, legal awareness, and government efforts to increase compliance with paying taxes have a significant effect on compliance with paying income tax in Muara Bangkahulu District. This shows the value of Fcount > Ftable (39.020 > 2.46) with a significant value of 0.000.